TIME-FREQUENCY NEXUS BETWEEN THE EASTERN EUROPEAN AND THE DEVELOPED STOCK MARKETS – THE CASE OF VISEGRAD GROUP - Živkov, Dejan; Mihajlović, Emilija; Kostić, Kristina (International Journal of Economic Practice and Policy, 2020)
This paper determines the level of interrelationship between the four stock markets of Visegrad group and the two major developed stock markets (Germany and the US). We endeavor to stipulate the dynamic connection via time domain as well as frequency domain, and for that purposs we apply wavelet coherence methodology. The results indicate that dark-red areas prevail around the World financial crisis and the European sovereign debt crisis, and they exist even at the high frequency areas (4 days) at DAX-PX and DAX-WIG, and somewhat DAX-BUX pairs. It is an indication of strong links between Visegrad group and DAX index, while the ties with the American index are slightly weaker. Slovakian SAX index has the widest areas of low correlation, whereas the presence of contagion cannot be found. This finding suggests that the Slovakian SAX index has the least synchronized movements with the two major stock indices, and thus can be used for diversification purposes in portfolios with DAX and S&P500.
Keywords: stock markets; Visegrad group; wavelet coherency; contagion and interdependence